Histamine production by human neutrophils. Issue 7 (9th April 2013) - Alcañiz, Lorena; Vega, Antonio; Chacón, Pedro; El Bekay, Rajaa; Ventura, Inmaculada; Aroca, Rocio; Blanca, Miguel; Bergstralh, Dan T.; Monteseirin, Javier
Abstract : Histamine is an important mediator in the development of allergic reactions. Only a small subset of human cell types is able to produce histamine. No previous studies have shown that human neutrophils are among them. The present work was undertaken to analyze whether human neutrophils produce histamine, and to determine what agonists are involved in histamine production by human neutrophils. The expression of histidine decarboxylase in human neutrophils was established by quantitative PCR, Western blotting, and flow cytometry analysis. The activity of the enzyme was determined by ELISA, which measured histamine in the culture supernatant of neutrophils stimulated with a set of classical agonists. Human neutrophils are bona fide histamine‐producing cells. Neutrophils store 0.29 pg/cell and release 50% of the histamine content in an antigen‐dependent manner and on stimulation with other neutrophil agonists. Basal expression of histidine decarboxylase, the rate‐limiting enzyme in histamine production, is higher in neutrophils from patients with allergies than from healthy donors. Our results cannot be ascribed to cell contamination for several reasons. LPS failed to induce histamine release by basophils, whereas it induced histamine release by neutrophils; and we did not detect basophils, monocytes, or lymphocytes in our neutrophil preparations. Eosinophils, albeit detected, were only 0.001‐0.004% of the final cell population, and they did not store or release histamine on antigen or LPS stimulation. Antigens to which patients with allergies were sensitized stimulated release of histamine from neutrophils. These observations represent a novel view of neutrophils as possible source of histamine in the allergic diseases.—Alcañiz, L., Vega, A., Chacón, P., El Bekay, R., Ventura, I., Aroca, R., Blanca, M., Bergstralh, D. T., Monteseirin, J. Histamine production by human neutrophils. FASEB J. 27, 2902–2910 (2013). www.fasebj.org